Orchestrated degradation behavior of Mg mesh for calvarial bone defect reconstruction - Ume Farwa; Seongsu Park; Myeongki Park; Ihho Park; Byoung-Gi Moon; Byong-Taek Lee (Journal of Magnesium and Alloys)
The biodegradability and biocompatibility of Mg alloys have rendered them favorable for cranial reconstruction applications. However, their rapid degradation rate has limited widespread use. In this study, we developed a Mg alloy -based mesh designed for calvarial bone defect reconstruction. We modulated the bone formation through the controlled degradation rate of the Mg alloy mesh. To achieve this, the Mg alloy mesh was coated with 2 types of coatings: Zn-d/Ca-P and Zn-d/Ca-P/P. Our findings revealed that, in comparison to the uncoated Mg alloy, both Zn-d/Ca-P and Zn-d/Ca-P/P coatings significantly reduced the degradation rate. The biocompatibility of the coated meshes improved markedly. With the Zn-d/Ca-P coating, there was not only an augmentation in the osteogenic potential of the Mg mesh but also an enhancement in angiogenic capacity. These meshed Mg samples were subsequently implanted into calvarial defects in rats. Bone regeneration was accelerated in specimens treated with Zn-d/Ca-P and Zn-d/Ca-P/P coatings compared to those with the bare Mg mesh. Furthermore, the in vivo assessments indicated that the coated meshes promoted angiogenesis. Nonetheless, the degradation rate of the Zn-d/Ca-P/P coating was slower than that of Zn-B/Ca-P. For applications requiring prolonged mechanical support, the Zn-d/Ca-P/P coating on Mg alloy is recommended, whereas the Zn-d/Ca-P coating is advisable for rapid regeneration where extended mechanical support is not critical.